Genome-wide association mapping of Fusarium crown rot resistance in Aegilops tauschii - Lin, Yu; Wang, Qing; Chen, Hao; Yan, Ning; Wu, Fangkun; Wang, Zhiqiang; Li, Caixia; Liu, Yaxi (Frontiers in Plant Science, 2022)
Fusarium crown rot (FCR), caused by various Fusarium species, is a primary fungal disease in most wheat-growing regions worldwide. Aegilops tauschii, the diploid wild progenitor of the D genome of common wheat, is a reservoir of genetic diversity for improving bread wheat biotic and abiotic resistance/tolerance. A worldwide collection of 286 Aegilops tauschii accessions was used to evaluate FCR resistance. Population structure analysis revealed that 115 belonged to the Aegilops tauschii ssp. strangulata subspecies, and 171 belonged to the Aegilops tauschii ssp. tauschii subspecies. Five accessions with disease index values lower than 20 showed moderate resistance to FCR. These five originated from Afghanistan, China, Iran, Uzbekistan, and Turkey, all belonging to the tauschii subspecies. Genome-wide association mapping using 6739 single nucleotide polymorphisms (SNPs) revealed that two SNPs on chromosome 2D and four SNPs on chromosome 7D were significantly associated with FCR resistance. Almost all FCR resistance alleles were presented in accessions from the tauschii subspecies, and only 4, 11, and 19 resistance alleles were presented in accessions from the strangulata subspecies. Combining phenotypic correlation analysis and genome-wide association mapping confirmed that FCR resistance loci were independent of flowering time, heading date, and plant height in this association panel. Six genes encoding disease resistance-related proteins were selected as candidates for further validation. The identified resistant Aegilops tauschii accessions will provide robust resistance gene sources for breeding FCR-resistant cultivars. The associated loci/genes will accelerate and improve FCR in breeding programs by deploying marker-assisted selection.